Analisa Pemeliharaan Mesin Printer Dengan Reliability Centred Maintenance (RCM) II Dan Life Cycle Cost (LCC) Di CV. XYZ - Timothy Anugrah Sugiarto; Endang Pudji W (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to optimize the maintenance of Banner printing machines at CV. XYZ Printing Company using the Reliability Centered Maintenance II (RCM II) and Life Cycle Cost (LCC) methods. RCM II is employed to identify and evaluate component failures, while LCC is utilized to calculate Costs throughout the machine's lifecycle. The study determines maintenance intervals for each component of the Banner printing machines. Subsequently, the Life Cycle Cost (LCC) is calculated to compare the maintenance Costs before and after implementing RCM II and LCC methods. The results reveal that the total Cost of maintenance after implementing RCM II and LCC is Rp. 258,424,522, which is lower than the previous total maintenance Cost of Rp. 300,000,000. Thus, the application of RCM II and LCC methods effectively optimizes the maintenance of Banner printing machines in a Cost-efficient manner. This research contributes to enhancing the effectiveness and efficiency of maintenance in the Banner printing industry.